Issledovanija F. Zadravca v oblasti sovremennogo slovenskogo romana - Sozina, Julija Anatol´evna (Slavistična revija, 2006)
The author gratefully acknowledge that the first volume of Franc Zadravec's Slovenski roman 20. stoletja Slovene 20th century novel in providing good theoretical support in writing her dissertation, i.e., the Slovene literary scholar's analyses to a certain extent influenced the conception and internal direction of her work.
Keywords: 20. st.; literarne študije; literarni zgodovinarji; literary historian; novel; roman; Slovene literature; slovenska književnost; Zadravec, Franc, 1925-